Impact of β-blockers on in-hospital mortality in patients with heart failure: a retrospective propensity-score matched analysis based on MIMIC-IV database - Wang, Xin; Zhang, Yuzhu; Xia, Jiangling; Xu, Hongyu; Zhang, Lu; Feng, Nianhai; An, Xiaona (Frontiers in Pharmacology, 2024)
This study assessed the relationship between β-blockers treatment and in-hospital mortality among individuals diagnosed with heart failure (HF). A retrospective cohort study was carried out on 9,968 HF patients sourced from the Medical Information Mart for Intensive Care (MIMIC)-IV database. Propensity score matching (PSM) was employed to balance the baseline differences. A multivariate regression analysis was utilized to evaluate the impact of β-blockers therapy on in-hospital mortality. Among the 9,968 patients, 6,439 (64.6%) were β-blockers users. Before matching, the overall inhospital mortality rate was 12.2% (1,217/9,968). Following PSM, a total of 3,212 patient pairs were successfully matched. The analysis revealed a correlation between β-blockers therapy and decreased in-hospital mortality (odds ratio 0.51 [0.43-0.60], P<0.001), as well as shorter Los (length of stay) hospital (β -1.43 [-1.96~-0.09], P<0.001). Notably, long-acting β-blockers treatment was linked to a decreased risk of in-hospital mortality (odds ratio 0.55 [0.46-0.65], P<0.001) and a shorter Los hospital (β -1.21 [-1.80~-0.63], P<0.001). Conversely, the research results did not show a notable decrease in-hospital mortality (odds ratio 0.66 [0.44-1.01], P=0.051) or Los hospital (β -1.01 [-2.27~-0.25], P=0.117) associated with short-acting β-blocker therapy. β-blockers therapy in the intensive care unit demonstrates potential benefits in lowering the risk of in-hospital mortality and reducing the duration of hospitalization among patients with HF. Specifically, long-acting β-blockers exhibit a protective effect by significantly decreasing both in-hospital mortality and Los hospital. Conversely, the study did not observe a substantial impact on in-hospital mortality or Los hospital duration in this cohort of patients following the administration of short-acting β-blockers.